THE ASPECTS OF MARXISM IN SOLOMON NORTHUP’S “TWELVE YEARS A SLAVE” - Raja Bobby Adytia; Syamsul Bahri (State University of Medan, 2016)
This study analyzes the Marxism conception towards the aspect of Marxism. Thedata were taken from the sentences or text produced in Twelve Years A Slavenovel of Solomon Northup in 1853 which has 199 pages. Particular attention isgiven to the concerning aspects of Marxism, as defined by Wood (2003). Thefocuses of the paper are to find out the aspects of Marxism in Twelve Years ASlave novel of Solomon Northup and also describe how Marxism are portrayed inthe novel based on the aspects. The results of the study are stated as follows: Theaspects of Marxism occurred are: Dialectical Materialism, Social Alienation,Exploitation of Class, and Economic Determinism. Then the aspects of Marxismfound in the novel of Twelve Years a Slave by Solomon Northup are portrayedthrough the difficulties of exploited and unfair treatment of being lower class.